A Phytoremediation of Chromium and Lead-Contaminated Soil Using Putative Raphanus raphanistrum - Simiyu, Gelas M.; Sheriff , Salia S.; Kinyua, Miriam G. (African Journal of Education,Science and Technology (AJEST), 2024)
Potentially toxic elements, including Chromium and Lead, naturally occur in the environment, however, human activities such as extensive farming, industrialization, and mining increase Potentially toxic element concentrations in soils. Hence, this study aimed to assess enhanced phytoremediation of Chromium and Lead-contaminated soils with putative mutant, Raphanus raphanistrum (wild radish). The putative plant was enhanced to phytoremediation of Chromium and Lead-contaminated soils. The soil physicochemical parameters pH, total organic matter, cation exchange capacity, and electrical conductivity determined were 5.20, 2.57%, 21.50 meq%, and 0.05 mS/cm, respectively. Raphanus raphanistrum seeds were treated with 0.00%, 0.25%, 0.50%, and 1.00% concentrations of colchicine to heighten growth and morphological development in enhanced phytoremediation of potentially toxic elements in soil. The treated Raphanus raphanistrum at 0.50% colchicine removed 226.69±1.22 mg/Kg and 236.95±0.82 mg/Kg of Chromium and 880.49±1.46 mg/Kg and 518.80±0.81 mg/Kg Lead in the first (M1) and second (M2) generations respectively. At the same treatment level, the putative plant hyperaccumulation potentially toxic elements at M1 and M2 generations absorbed 68.60% and 22.00% of Chromium and Lead, respectively. The plant bioaccumulated high amounts of metal elements, Chromium and Lead, capable of causing potential environmental and health concerns. This study finding contributes significantly to phytoremediation techniques in ecological restoration and recommends putative R. raphanistrum for Chromium and Lead polluted soil decontamination.